Effects of salt stress on plant growth characteristics and mineral content in diverse rice genotypes. Issue 3 (4th May 2017) - Thu, Thieu Thi Phong; Yasui, Hideshi; Yamakawa, Takeo
ABSTRACT: When rice is grown under moderate salinity (6 dS m −1 ), yields are reduced by up to 50%. The development of salt-tolerant varieties is a key strategy for increasing yields. We conducted an experiment using a hydroponic system with ion components similar to seawater to determine useful parameters for assessing salt tolerance. Two-week-old seedlings were grown for 7 days on Yoshida hydroponic solution. The treatment group then additionally received an artificial seawater solution (electrical conductivity, 12 dS m −1 ). After a 2-week period of salt stress, standard evaluation scores (SES) of visual salt injuries were assessed. The K, Na, Mg, and Ca contents were then determined in the roots, sheaths, and leaves of each plant. Following the SES results, we divided the 37 genotypes into four groups: salt-tolerant groups (STGs), moderately salt-tolerant groups, salt-sensitive groups (HSSGs), and highly salt-sensitive groups (HSSGs). In the control, STGs had the highest sheath K content (30.1 mg g −1 dried weight [DW]), whereas HSSGs had the lowest (21.4 mg g −1 DW). Sheath K was also highly and negatively correlated with SES. This suggests that sheath K may be useful for identifying salt-tolerant varieties under non-saline conditions. Plant growth was significantly affected under salt stress, but STGs had the smallest decrease in sheath DW. SES was significantly correlated with sheath and leaf Na, sheath K and Mg, and sheath and leaf Na/K and Na/Mg ratios. The results suggested that sheath K, Na/K, and Na/Mg may be useful indicators for genetic analyses of salt-tolerant varieties under salt-stress conditions. The salt-tolerant cultivars, KCR20, KCR124, and KCR136, are possible candidates for such studies because they had high sheath K content (31.19, 31.21, 29.44 mg g −1 DW, respectively) under non-saline conditions and low SES (3.3, 3.6, 3.9, respectively), and low sheath Na/K (0.64, 0.52, 0.92, respectively) and Na/Mg ratios (2.96, 2.27, 3.03, respectively) under salt-stress conditions.